Characterizations of $δ_1\text{-}{β}_{\mathcal{I}}$-paracompactness concerning an ideal (European Journal of Pure and Applied Mathematics, 2025)
Al-Jarrah presented and examined the idea of β1-paracompactness in topological spaces, whereas Qahis extended the original idea of β1-paracompact spaces by further developing and investigating the idea of β1-paracompact spaces with respect to an ideal. This work analyzes the properties, subsets, and subspaces of δ1-βI-paracompact spaces, which are wider in scope thanthe β1-paracompact spaces delineated by Qahis. Furthermore, we investigate the invariants of δ1-βI-paracompact spaces via the view of functions.
Keywords: ideal topological space; $δ_1\text{-}{β}_{\mathcal{I}}$-paracompact; $δ\text{-}{β}_{\mathcal{I}}$-open